Checklist of oribatid mites (Acari: Oribatida) from peatlands in the United States with notes on oribatid mites from a bog in Minnesota - Barreto, Carlos; Lindo, Zoë (Zootaxa, 2024)
Peatlands are important ecosystems for carbon storage worldwide and often contain unique species. Oribatid mites are the dominant soil arthropods in terrestrial systems like peatlands, where they show high diversity, yet are under-sampled. To create a checklist of oribatid mite species from peatlands in the U.S., we collected a total of 53 peat-soil samples between 2015 and 2020 from a peatland located at the Marcell Experimental Forest in Minnesota, U.S. that yielded an assemblage of 27 families, 43 genera and 49 species; species richness estimates range between 56–102 species. We compiled a final checklist with data from previous studies of American peatlands available online up until July 2024 that revealed an additional 107 species for a total of 156 species distributed in 83 genera and 27 families known from peatlands in the U.S. From our samples, Punctoribates palustris is present in the most states (N=6), and is known to be associated with Sphagnum mosses in North America. Other common peatland species such as Eniochthonius mahunkai, Mainothrus badius and Limnozetes lustrum were also abundant at our site. However, we also found species typical of drier environments (e.g., dry forests, dry montane regions, canopy habitats) such as Eueremaeus nr. proximus, Scapheremaeus palustris, and Cepheus corae. Thus, our results reinforce the idea that peatlands may have a specific subset of species that are common to these ecosystems, but that in general many different species can be occasionally found in peatlands.